Mullerian Adenosaroma of the Cervix with Sarcomatous Overgrowth and Heterologous Elements Presenting as a Recurrent Cervical Polyp. (16th August 2012) - Charfi, Slim; Kallel, Rim; Mnif, Hela; Ellouze, Sameh; Dhouib, Mohamed; Guermazi, Mohamed; Khabir, Abdelmajid; Sellami-Boudawara, Tahya
Abstract : Mullerian adenosarcoma of the cervix is a rare tumor composed of benign epithelial and malignant stromal components. Sarcomatous overgrowth and heterologous elements in cervical adenosarcoma are extremely infrequent. We report the case of a 26-year-old woman admitted at the gynaecology department for a painless mass protruding from her vagina. The initial pathological exam concluded to endocervical polyp. Six months later, the patient was readmitted with a recurrence of the polyp. The pathological exam demonstrated interlacing fascicles of elongated spindle cells with few mitotic activity and no glandular formation. After reviewing of the initial polyp the diagnosis of mullerian adenosarcoma was suggested. A second recurrence of the polyp was noted one month later. Histopathological exam of the recurrent polyp confirmed the diagnosis of adenosarcoma with sarcomatous overgrowth and heterologous elements. The patient was lost for follow-up. Cervical adenosarcoma with sarcomatous overgrowth and heterologous element is a rare tumor that occurs in younger age in contrast to endometrium/corpus uterin mullerian adenosarcoma. In young women with recurrent cervical polyp, mullerian adenosarcoma must be considered and should be excluded by careful histopathological exam. Sarcomatous overgrowth and myometrial invasion are the most important prognostic factors. Treatment strategy is still unclear.